Alterations in cortical thickness in nonmedicated premature ejaculation patients: A morphometric MRI study - Guo, Fan; Xi, Yi‐Bin; Gao, Ming; Liu, Lin; Fei, Ning‐Bo; Qin, Wei; Li, Chen; Cui, Long‐Biao; Yan, Fei; Yu, Lei; Yuan, Jian‐Lin; Yin, Hong (Journal of magnetic resonance imaging, 2018)
Purpose Premature ejaculation (PE) is one of the most common sexual dysfunctions in men. However, there has been little research evaluating alterations in brain structure related to PE. We aimed to investigate the characteristics of nonmedicated PE patients in terms of brain morphometry. Materials and Methods The sample consisted with 32 medication‐naïve adult men with clinical diagnosed PE and matched 31 healthy controls. All participants received diagnostic interviews and 3.0 Tesla MRI scans. Automatic segmentation processing of MRI structure images was performed using FreeSurfer software and cerebral cortical thickness between groups was compared. Results The PE group had thicker cortex in widespread regions, including the frontal, parietal and occipital lobe, and limbic system, compared with the healthy control group (P < 0.05). Moreover, the duration is negatively correlated with the mean cortical thickness of the right medial orbitofrontal cortex, right precentral gyrus and left superior frontal cortex (R2 = 0.29, P < 0.003; R2 = 0.163, P < 0.04; R2 = 0.2, P < 0.02), while the Premature Ejaculation Diagnostic Tool score is negatively correlated with the mean cortical thickness of the left caudal middle frontal cortex (R2 = 0.33, P < 0.005). Conclusion The result highlights the structural features of PE and suggests the relationship with the severity of impairment is related to the severity of anatomic abnormality with the relevant brain region. These results support the value of imaging measures as markers for understanding the physiopathology of PE. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:656–662.